Podcast
Questions and Answers
What is the result of the expression $-|-2| + (-3-2)² - (-5+2)⁰$?
What is the result of the expression $-|-2| + (-3-2)² - (-5+2)⁰$?
22
What is the x-intercept of the equation $y=-3x+6$?
What is the x-intercept of the equation $y=-3x+6$?
(2,0)
What is the result of the expression $-|-3-2³| + 2 × 6² - 6$?
What is the result of the expression $-|-3-2³| + 2 × 6² - 6$?
55
If $f(x)= 4-x²$, what is $f(-2)$?
If $f(x)= 4-x²$, what is $f(-2)$?
What is the result of the expression $(14a⁴b⁻⁷) ÷ (42b⁷a⁵)$?
What is the result of the expression $(14a⁴b⁻⁷) ÷ (42b⁷a⁵)$?
Evaluate $2x²-3y-3z$ if $x=-2$, $y=3$ and $z=-5$.
Evaluate $2x²-3y-3z$ if $x=-2$, $y=3$ and $z=-5$.
Translate the following sentence into an algebraic expression: The product of a number and six is three times the same number less than ten.
Translate the following sentence into an algebraic expression: The product of a number and six is three times the same number less than ten.
Solve the inequality $3(5x-1) < 4(x-6)$.
Solve the inequality $3(5x-1) < 4(x-6)$.
Find the solutions for $x$ in the equation $(3x+2)(x-4) = 0$.
Find the solutions for $x$ in the equation $(3x+2)(x-4) = 0$.
Multiply the binomials $(3x-5)(2x+5)$.
Multiply the binomials $(3x-5)(2x+5)$.
Solve for $x$: $3(x-5) - 4x = 6(x-10) - (x+5)$.
Solve for $x$: $3(x-5) - 4x = 6(x-10) - (x+5)$.
Simplify the expression $-[-5-(2+x)] - 2(-5+2x)$.
Simplify the expression $-[-5-(2+x)] - 2(-5+2x)$.
Solve the system of equations: $2x-5y=-4$, $x+6y=15$.
Solve the system of equations: $2x-5y=-4$, $x+6y=15$.
Write the equation that passes through the points (-3,-16) and (0,-10).
Write the equation that passes through the points (-3,-16) and (0,-10).
Simplify the expression $-3(x-5x²) + 3x² - 6x$.
Simplify the expression $-3(x-5x²) + 3x² - 6x$.
Simplify the expression $-10(x+4) - 5(-x+6x)$.
Simplify the expression $-10(x+4) - 5(-x+6x)$.
Simplify the expression $√(a³b⁷z³)$.
Simplify the expression $√(a³b⁷z³)$.
Find the perpendicular slope of the line $3x-9y=15$.
Find the perpendicular slope of the line $3x-9y=15$.
Factor the quadratic $5x²-17x+14$.
Factor the quadratic $5x²-17x+14$.
Simplify the expression $3 + 2 × 3 ÷ (-2+3)²$.
Simplify the expression $3 + 2 × 3 ÷ (-2+3)²$.
Solve $2|5x-4| - 6 = 10$.
Solve $2|5x-4| - 6 = 10$.
What is $(3/x)-(2/y)$?
What is $(3/x)-(2/y)$?
Factor the quadratic $7z²+60z-27$.
Factor the quadratic $7z²+60z-27$.
Factor the quadratic $2x²+25x+50$.
Factor the quadratic $2x²+25x+50$.
What is $(2ⁿ)ⁿ + n²$ if $n=2$?
What is $(2ⁿ)ⁿ + n²$ if $n=2$?
If $f(x) = 2x²+5x-6$, what is $f(x+3)$?
If $f(x) = 2x²+5x-6$, what is $f(x+3)$?
Solve for $x$: $ax+by=cd$.
Solve for $x$: $ax+by=cd$.
What is $√225 + √900$?
What is $√225 + √900$?
If the original price of an item was $30 and Joan only paid $24, what was the percentage of the discount Joan received?
If the original price of an item was $30 and Joan only paid $24, what was the percentage of the discount Joan received?
What is $(30/7) ÷ (-19/5)$?
What is $(30/7) ÷ (-19/5)$?
Solve: $(4/x) = (12/7.5)$.
Solve: $(4/x) = (12/7.5)$.
What is 0.0000968 in scientific notation?
What is 0.0000968 in scientific notation?
What is 968000 in scientific notation?
What is 968000 in scientific notation?
Solve: $4x²-16x+16=0$.
Solve: $4x²-16x+16=0$.
$₃√(27x³y⁶)+√(4x²y⁴)$ results in what expression?
$₃√(27x³y⁶)+√(4x²y⁴)$ results in what expression?
Multiply the expressions $(3x+2y)(x-3y)$.
Multiply the expressions $(3x+2y)(x-3y)$.
If $g(x) = 3x²+4x-7$, what is $g(-1)$?
If $g(x) = 3x²+4x-7$, what is $g(-1)$?
Solve the equation: $½(3x+5) - ½x = ¾(x+1)$.
Solve the equation: $½(3x+5) - ½x = ¾(x+1)$.
Solve the inequality $2(x+3) - 4x > 6(2x-1)$.
Solve the inequality $2(x+3) - 4x > 6(2x-1)$.
Study Notes
Mathematical Expressions and Solutions
- Evaluating expressions such as -|-2| + (-3-2)² - (-5+2)⁰ results in a total of 22.
- The x-intercept for the linear equation y = -3x + 6 can be found at (2,0).
- Another expression, -|-3-2³| + 2 × 6² - 6, simplifies to 55.
- For the function f(x) = 4 - x², computing f(-2) yields 0.
Algebraic Manipulations
- Dividing the expression (14a⁴b⁻⁷) by (42b⁷a⁵) gives a simplified result of 1/3ab¹⁴.
- Evaluating the expression 2x² - 3y - 3z at x = -2, y = 3, z = -5 results in 14.
- Translating a sentence into an algebraic expression: "The product of a number and six is three times the same number less than ten" gives 6x = 10 - 3x.
- An inequality, 3(5x - 1) < 4(x - 6), simplifies to x < -21/11.
Solutions to Equations and Systems
- The solutions for x in the equation (3x + 2)(x - 4) = 0 are x = -2/3 and x = 4.
- Multiplying out (3x - 5)(2x + 5) results in 6x² + 5x - 25.
- Solving 3(x - 5) - 4x = 6(x - 10) - (x + 5) leads to x = 25/3.
- Simplifying expressions like -[-5 - (2 + x)] - 2(-5 + 2x) yields 17 - 3x.
Systems of Equations and Linear Functions
- The solution to the system of equations 2x - 5y = -4 and x + 6y = 15 is (3, 2).
- The equation passing through points (-3, -16) and (0, -10) can be written as y = 2x - 10.
Further Simplifications and Factoring
- The expression -3(x - 5x²) + 3x² - 6x simplifies to 18x² - 9x.
- Simplifying -10(x + 4) - 5(-x + 6x) results in -35x - 40.
- The expression √(a³b⁷z³) simplifies to ab³z√(abz).
Slope and Factoring
- The perpendicular slope for the line represented by 3x - 9y = 15 is -3.
- Factoring the expression 5x² - 17x + 14 gives (5x - 7)(x - 2).
- Further factoring 7z² + 60z - 27 leads to (7z - 3)(z + 9).
- The expression 2x² + 25x + 50 can be factored as (2x + 5)(x + 10).
Special Values and Properties
- For n = 2 in the expression (2ⁿ)ⁿ + n², the result is 20.
- Evaluating f(x) = 2x² + 5x - 6 at x + 3 results in 2x² + 17x + 27.
- Extracting a square root √225 + √900 gives a result of 45.
- If the original price of an item was $30 and the paid price was $24, the discount percentage is 20%.
Operations and Simplified Outcomes
- The division (30/7) ÷ (-19/5) simplifies to (-150/133).
- To solve (4/x) = (12/7.5), the result is 2.5.
- Converting .0000968 to scientific notation yields 9.68 × 10⁻⁵ and 968000 converts to 9.68 × 10⁵.
- The quadratic equation 4x² - 16x + 16 = 0 has a solution of x = 2.
- The expression ₃√(27x³y⁶) + √(4x²y⁴) simplifies to 5xy².
- The product (3x + 2y)(x - 3y) expands to 3x² - 7xy - 6y².
- Evaluating g(x) = 3x² + 4x - 7 at x = -1 gives -8.
- Solving the equation ½(3x + 5) - ½x = ¾(x + 1) results in -7.
- The inequality 2(x + 3) - 4x > 6(2x - 1) leads to x > 6/7.
Studying That Suits You
Use AI to generate personalized quizzes and flashcards to suit your learning preferences.
Description
Test your knowledge of basic math concepts with these PERT Math flashcards. Each card covers different mathematical expressions and equations, helping you enhance your problem-solving skills. Perfect for students preparing for the PERT exam!